2016
DOI: 10.1111/bjh.14317
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for evaluation of treatment response in classical Hodgkin lymphoma: comparison of sGalectin‐1, sCD163 and sCD30 with TARC

Abstract: Soluble Galectin-1 (sGal-1, also termed LGALS1), soluble CD163 (sCD163) and soluble CD30 (sCD30) have been reported to be elevated in plasma or serum of patients with classical Hodgkin lymphoma (cHL). We aimed to determine the clinical utility of these biomarkers for evaluation of treatment response compared to thymus and activation regulated chemokine (TARC, also termed CCL17). Plasma or serum samples were prospectively collected among 103 newly diagnosed cHL patients before and after treatment. Levels of sGa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
42
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 33 publications
(55 reference statements)
9
42
1
Order By: Relevance
“…We also found that miRs tended to reach the levels of those found in controls. In addition, the levels of sCD14 and sCD30 remained higher compared to the control group but decreased after chemotherapy, which is also in agreement with other studies [62,64].…”
Section: Discussionsupporting
confidence: 92%
“…We also found that miRs tended to reach the levels of those found in controls. In addition, the levels of sCD14 and sCD30 remained higher compared to the control group but decreased after chemotherapy, which is also in agreement with other studies [62,64].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the survival parameters, we found that the Kyn/Trp ratio was significantly associated with PFS, whereas none of the seven component factors of the IPS for advanced HL, nor the serum sCD30 level, was significantly associated with PFS. This observation that only the serum Kyn/Trp ratio was significantly associated with shorter PFS should attract attention because it indicates the importance of Trp catabolism in the pathogenesis of HL.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the survival parameters, we found that the Kyn/Trp ratio was significantly associated with PFS, whereas none of the seven component factors of the IPS for advanced HL, 17 nor the serum sCD30 level, [26][27][28][29][30] Most research in this area to date has focused on IDO as the central and immunobiologically relevant enzyme that catalyzes the conversion of Trp to Kyn. However, there are two other enzymes, tryptophan 2,3dioxygenase and IDO2, that also catalyze the same enzymatic step.…”
mentioning
confidence: 92%
“…Blood-based biomarkers are ideally suited to provide answers to those questions; for example, serum TARC, galectin-1, and CD163 have emerged as promising tools to assess interim response to chemotherapy in addition to PET. 136,137 Moreover, detection of tumor-specific mutations or CN variations in cell-free circulating tumor DNA by next-generation sequencing techniques or digital droplet polymerase chain reaction have been shown to be feasible in patients with cHL and provide unique opportunities for real-time disease monitoring and quantitative assessment of minimal residual disease. [138][139][140]…”
Section: Biomarker-driven Prognostication and Risk Stratification In Chlmentioning
confidence: 99%